Mapping Hydrothermal Alteration at the Fentale-Dofan Magmatic Segment of the Main Ethiopian Rift - Raggiunti, Martina; Keir, Derek; Pagli, Carolina (Frontiers in Earth Science, 2021)
The Main Ethiopian Rift (MER) is characterized by extensional tectonics and volcanism, associated with active hydrothermal systems and hydrothermal deposits. The spatial distribution of these deposits, its link with faults and rocks types provides important clues to what controls fluid flow in the subsurface. However, little is known about it in the East African rift. We address this issue with a multidisciplinary approach in the Fentale-Dofan magmatic segment of the MER, an area characterized by intense volcanic and tectonic activities and a geothermal prospect. Primarily we conduct mapping of hydrothermal deposits and rock lithologies using a surface feature classification technique of multispectral satellite images. We then interpret the map using a new database of faults and active hydrothermal features such as hot-springs and fumaroles. We find that the surface hydrothermal deposits are mainly focused near Fentale and Dofan volcanoes. At Dofan the hydrothermal alterations are focused on rhyolites on the western side of the volcano, in an area of intense rift parallel faults. At Fentale volcano the hydrothermal alterations are mainly associated with ignimbrite and show a circular pattern around the volcanic edifice, but also in places follow the NNE striking faults. The association between hydrothermal deposits with either the rhyolites and ignimbrites is likely due to them being relatively easily altered (in comparison to basalt), and also their brittle nature allows for fracturing through which localized fluid flow can occur (as opposed to the sediments). At Fentale, the more complex association of hydrothermal deposits and active features around the edge of the ignimbrite suggests formation contacts may also localize fluid flow in places. The presence of hydrothermal deposits and active hydrothermal manifestations, along with other lines of evidence such as locus of subsurface dike intrusion and reduction of seismogenic layer thickness at the volcanic centres, suggest that discrete and localized magma reservoirs beneath Fentale and the DVC is the heat source for hydrothermal circulation.